A yarn-reinforced nanofibril composite aerogel fiber and a preparation method thereof
By wrapping a modified nano-zinc oxide aerogel layer around aramid 1313 yarn and combining it with supercritical drying technology, the problem of insufficient strength of aerogel fibers was solved, and yarn-reinforced nano-aramid composite aerogel fibers with high strength and antibacterial properties were prepared.
Patent Information
- Application Number
- CN202511615045.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-02-03
- Estimated Expiration
- 2045-11-06
AI Technical Summary
Existing aerogel fibers have poor strength due to their porous structure, which affects the quality of textiles.
Aramid 1313 yarn was used as the skeleton and wrapped with an aerogel layer of modified nano-zinc oxide. Yarn-reinforced nano-aramid composite aerogel fiber was prepared by sol-gel method and supercritical drying technology. The modified nano-zinc oxide and potassium hydroxide formed a three-dimensional network structure, and the porous structure was preserved by supercritical carbon dioxide drying technology.
It improves the strength and antibacterial properties of the fibers while maintaining the porous structure and thermal insulation properties of the aerogel, thus enhancing the quality of the textiles.
Abstract
Description
Technical Field
[0001] This invention relates to the field of aerogel fibers, specifically to a yarn-reinforced nano-aramid composite aerogel fiber and its preparation method. Background Technology
[0002] Aerogel fibers are functional materials that combine the nanoporous structure of aerogels with the fibrous morphology. Based on the sol-gel method and produced through processes such as supercritical drying, they possess both the low density and high specific surface area of aerogels and the flexibility and weavability of fibers. Their three-dimensional network pore structure endows them with excellent thermal insulation, sound insulation, and adsorption properties. Currently, aerogel fibers are widely used in aerospace thermal insulation materials, outdoor thermal clothing, high-efficiency energy storage electrodes, and air purification filter materials.
[0003] Patent CN119041047B discloses a PBO aerogel fiber and its preparation method, including the following steps: (1) preparing a polyhydroxyamide (PHA) spinning solution; (2) extruding the PHA spinning solution from a spinneret into a coagulation bath to spin PHA-PBO wet aerogel fibers; (3) freeze-drying the PHA-PBO wet aerogel fibers to obtain PHA-PBO aerogel fibers; (4) heating the PHA-PBO aerogel fibers to obtain PBO aerogel fibers. However, the existing solution still has some shortcomings: although the porous structure of aerogel fibers gives the fibers excellent thermal insulation properties, it also leads to poor fiber strength, affecting the quality of textiles. Summary of the Invention
[0004] The purpose of this invention is to provide a yarn-reinforced nano-aramid composite aerogel fiber and its preparation method, so as to solve the problems existing in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a yarn-reinforced nano-aramid composite aerogel fiber, comprising aramid 1313 yarn and an aerogel layer wrapped around it; the aerogel layer is prepared from aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, modified nano zinc oxide, anhydrous ethanol, deionized water and acetic acid; the modified nano zinc oxide is prepared from nano zinc oxide, ethanol aqueous solution, γ-aminopropyltriethoxysilane and acetic acid.
[0006] Furthermore, the fineness of aramid 1313 yarn is 3.1-3.3 dtex.
[0007] Furthermore, the particle size of the nano zinc oxide is 20-40 nm.
[0008] Furthermore, the aramid 1313 chopped fibers have a length of 2-3 mm and a diameter of 12-14 μm.
[0009] Furthermore, a method for preparing yarn-reinforced nano-aramid composite aerogel fiber includes the following steps:
[0010] (1) Immerse the aramid 1313 yarn in acetone solvent and clean it for 10-20 minutes under ultrasonic power of 300-400W and frequency of 40-45kHz, and then dry it at 60-80℃ for later use.
[0011] Nano zinc oxide is added to an ethanol aqueous solution with a mass fraction of 50-70% and treated with an ultrasonic device with a power of 200-400W for 30-40 minutes. Then, γ-aminopropyltriethoxysilane is added, and the pH value is adjusted to 5.5-6.0 with acetic acid. The mixture is stirred in a closed container at 50-60℃ and 200-300rpm for 1-2 hours. After filtration, the mixture is washed 2-4 times with anhydrous ethanol and then placed in a vacuum drying oven at 70-80℃ for 4-6 hours to obtain modified nano zinc oxide.
[0012] (2) Add aramid 1313 short-cut fibers to dimethyl sulfoxide solvent, add potassium hydroxide, stir at room temperature at 200-300 rpm for 5-7 days under nitrogen protection, then add modified nano zinc oxide, and disperse for 20-40 minutes under ultrasonic power of 400-600W to obtain nano aramid fiber sol.
[0013] (3) Pass the aramid 1313 yarn pretreated in step (1) through an impregnation tank containing the nano aramid fiber sol obtained in step (2) at a speed of 0.5-1.5 m / min.
[0014] (4) Pass the impregnated aramid 1313 yarn through a coagulation bath, which includes anhydrous ethanol, deionized water and acetic acid;
[0015] (5) The gelled fibers are placed in 50-60% ethanol aqueous solution and 70-80% ethanol aqueous solution for 8-12 minutes each, and finally placed in anhydrous ethanol at room temperature for 10-14 hours.
[0016] (6) Then the fiber is placed in an autoclave and solvent is replaced with liquid carbon dioxide. The replacement is carried out for 3-4 hours at a temperature of 30-35℃ and a pressure of 7-8MPa. Then the temperature is raised to 40-45℃ and the pressure is increased to 10-12MPa and maintained for 1-2 hours. Finally, the pressure is released to atmospheric pressure at a rate of 0.5-1MPa / h.
[0017] (7) Finally, the fiber is heat-treated in a hot air oven at 80-100℃ for 0.5-1 hours to obtain composite aerogel fiber.
[0018] Furthermore, in step (1), the mass ratio of nano zinc oxide, aqueous ethanol solution and γ-aminopropyltriethoxysilane is 100:(400-420):(5-8).
[0019] Furthermore, in step (2), the mass ratio of aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, and modified nano zinc oxide is 1:(500-520):(1-2):(0.05-0.15).
[0020] Furthermore, the soaking time in step (3) is 2-3 minutes.
[0021] Furthermore, in step (4), the mass ratio of anhydrous ethanol, deionized water and acetic acid in the coagulation bath is (45-55):(45-55):(10-20).
[0022] Furthermore, in step (4), the coagulation bath residence time is 1-2 minutes.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] 1. Acetone was used to ultrasonically clean the aramid 1313 yarn. As an organic solvent, acetone effectively dissolved and removed oil and impurities from the surface of the aramid 1313 yarn, providing a clean interface for the subsequent adhesion of the aerogel coating. Subsequently, dimethyl sulfoxide was used as a solvent and potassium hydroxide as an alkaline catalyst to nano-size the aramid 1313 chopped fibers. Potassium hydroxide acted on the amide groups on the aramid molecular chain, causing a deprotonation reaction to generate negatively charged amide anions. Through electrostatic repulsion, the aramid 1313 chopped fibers dissociated into nano-aramid fibers. Then, nano-zinc oxide modified with γ-aminopropyltriethoxysilane was added and ultrasonically dispersed to ensure uniform distribution. The nano-zinc oxide served as an antibacterial component. After the pretreated yarn was impregnated in the nano-aramid fiber sol, acetic acid was used as a proton source in the coagulation bath to neutralize the negative charge on the surface of the nano-aramid fibers, promoting the regeneration of amide groups and forming a three-dimensional network structure through intermolecular hydrogen bonding, thus achieving gelation and fixation. Dimethyl sulfoxide (DMSO) and moisture are removed through gradient ethanol replacement, followed by supercritical carbon dioxide drying technology. Utilizing the zero surface tension of carbon dioxide in its supercritical state, ethanol is removed without damaging the porous structure, ultimately forming a composite aerogel fiber encapsulated in aerogel. The high specific surface area aerogel layer is tightly bonded to the aramid 1313 yarn through mechanical interlocking and hydrogen bonding. Nano-zinc oxide is distributed within the aerogel pores, achieving antibacterial properties. Detailed Implementation
[0025] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0026] A yarn-reinforced nano-aramid composite aerogel fiber includes aramid 1313 yarn and an outer aerogel layer thereon; the aerogel layer is prepared from aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, modified nano zinc oxide, anhydrous ethanol, deionized water and acetic acid; the modified nano zinc oxide is prepared from nano zinc oxide, ethanol aqueous solution, γ-aminopropyltriethoxysilane and acetic acid.
[0027] Where specific experimental steps or conditions are not specified in the examples, they can be performed according to the conventional experimental steps or conditions described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products. Example
[0028] (1) Immerse aramid 1313 yarn with a fineness of 3.1 dtex in acetone solvent, clean it for 10 minutes under ultrasonic power of 300W and frequency of 40kHz, and then dry it at 60℃ for later use.
[0029] Nano-zinc oxide with a particle size of 20 nm was added to a 50% (w / w) aqueous ethanol solution and treated with an ultrasonic device with a power of 200 W for 30 minutes. Then, γ-aminopropyltriethoxysilane was added, and the pH value was adjusted to 5.5 with acetic acid. The mixture was stirred in a sealed container at 50 °C and 200 rpm for 1 hour. After filtration, the mixture was washed twice with anhydrous ethanol and then placed in a vacuum drying oven at 70 °C for 4 hours to obtain modified nano-zinc oxide. The mass ratio of nano-zinc oxide, aqueous ethanol solution, and γ-aminopropyltriethoxysilane was 100:400:5.
[0030] (2) Add 2 mm long and 12 μm diameter aramid 1313 short chopped fibers to dimethyl sulfoxide solvent, add potassium hydroxide, stir at 200 rpm for 5 days under nitrogen protection at room temperature, then add modified nano zinc oxide, and disperse for 20 minutes under ultrasonic power of 400 W to obtain nano aramid fiber sol.
[0031] The mass ratio of aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, and modified nano zinc oxide is 1:500:1:0.05.
[0032] (3) Pass the aramid 1313 yarn pretreated in step (1) through an impregnation tank containing the nano aramid fiber sol obtained in step (2) at a speed of 0.5 m / min for 2 minutes.
[0033] (4) Pass the impregnated aramid 1313 yarn through a coagulation bath for 1 minute; the coagulation bath includes anhydrous ethanol, deionized water and acetic acid, and the mass ratio of anhydrous ethanol, deionized water and acetic acid in the coagulation bath is 45:45:10.
[0034] (5) The gelled fibers were placed in 50% ethanol aqueous solution and 70% ethanol aqueous solution for 8 minutes each, and then left to stand in anhydrous ethanol at room temperature for 10 hours.
[0035] (6) Then the fiber is placed in an autoclave and replaced with liquid carbon dioxide for 3 hours at a temperature of 30°C and a pressure of 7MPa. Then the temperature is raised to 40°C, the pressure is increased to 10MPa and maintained for 1 hour. Finally, the pressure is released to atmospheric pressure at a rate of 0.5MPa / h.
[0036] (7) Finally, the fiber was heat-treated in an 80°C hot air oven for 0.5 hours to obtain composite aerogel fiber. Example
[0037] (1) Immerse aramid 1313 yarn with a fineness of 3.2 dtex in acetone solvent, clean it for 15 minutes under ultrasonic power of 350W and frequency of 42.5kHz, and then dry it at 70℃ for later use.
[0038] Nano-zinc oxide with a particle size of 30 nm was added to a 60% (w / w) aqueous ethanol solution and treated with an ultrasonic device with a power of 300 W for 35 minutes. Then, γ-aminopropyltriethoxysilane was added, and the pH was adjusted to 5.7 with acetic acid. The mixture was stirred in a sealed container at 55 °C and 250 rpm for 1.5 hours. After filtration, the mixture was washed three times with anhydrous ethanol and then placed in a vacuum drying oven at 75 °C for 5 hours to obtain modified nano-zinc oxide. The mass ratio of nano-zinc oxide, aqueous ethanol solution, and γ-aminopropyltriethoxysilane was 100:410:6.5.
[0039] (2) Add 2.5 mm long and 13 μm diameter aramid 1313 short chopped fibers to dimethyl sulfoxide solvent, add potassium hydroxide, stir at 250 rpm at room temperature for 6 days under nitrogen protection, then add modified nano zinc oxide, and disperse for 30 minutes under ultrasonic power of 500 W to obtain nano aramid fiber sol.
[0040] The mass ratio of aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, and modified nano zinc oxide is 1:510:1.5:0.1.
[0041] (3) Pass the aramid 1313 yarn pretreated in step (1) through an impregnation tank containing the nano aramid fiber sol obtained in step (2) at a speed of 1 m / min for 2.5 minutes.
[0042] (4) Pass the impregnated aramid 1313 yarn through a coagulation bath for 1.5 minutes. The coagulation bath consists of anhydrous ethanol, deionized water and acetic acid, and the mass ratio of anhydrous ethanol, deionized water and acetic acid in the coagulation bath is 50:50:15.
[0043] (5) The gelled fibers were placed in 55% ethanol aqueous solution and 75% ethanol aqueous solution for 10 minutes each, and finally placed in anhydrous ethanol at room temperature for 12 hours.
[0044] (6) Then the fiber was placed in an autoclave and solvent was replaced with liquid carbon dioxide. The replacement was carried out for 3.5 hours at a temperature of 32.5℃ and a pressure of 7.5MPa. Then the temperature was raised to 42.5℃, the pressure was increased to 11MPa and maintained for 1.5 hours. Finally, the pressure was released to atmospheric pressure at a rate of 0.75MPa / h.
[0045] (7) Finally, the fiber was heat-treated in a 90℃ hot air oven for 0.75 hours to obtain composite aerogel fiber. Example
[0046] (1) Immerse aramid 1313 yarn with a fineness of 3.3dtex in acetone solvent, clean it for 20 minutes under ultrasonic power of 400W and frequency of 45kHz, and then dry it at 80℃ for later use.
[0047] 40 nm nano-zinc oxide was added to a 70% (w / w) aqueous ethanol solution and treated with an ultrasonic device at 400 W for 40 minutes. Then, γ-aminopropyltriethoxysilane was added, and the pH was adjusted to 6.0 with acetic acid. The mixture was stirred in a sealed container at 60 °C and 300 rpm for 2 hours. After filtration, the mixture was washed four times with anhydrous ethanol and then placed in a vacuum drying oven at 80 °C for 6 hours to obtain modified nano-zinc oxide. The mass ratio of nano-zinc oxide, aqueous ethanol solution, and γ-aminopropyltriethoxysilane was 100:420:8.
[0048] (2) Add 3 mm long and 14 μm diameter aramid 1313 short chopped fibers to dimethyl sulfoxide solvent, add potassium hydroxide, stir at 300 rpm at room temperature for 7 days under nitrogen protection, then add modified nano zinc oxide, and disperse for 40 minutes under ultrasonic power of 600 W to obtain nano aramid fiber sol.
[0049] The mass ratio of aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, and modified nano zinc oxide is 1:520:2:0.15.
[0050] (3) Pass the aramid 1313 yarn pretreated in step (1) through an impregnation tank containing the nano aramid fiber sol obtained in step (2) at a speed of 1.5 m / min for 3 minutes.
[0051] (4) Pass the impregnated aramid 1313 yarn through a coagulation bath for 2 minutes; the coagulation bath includes anhydrous ethanol, deionized water and acetic acid, and the mass ratio of anhydrous ethanol, deionized water and acetic acid in the coagulation bath is 55:55:20.
[0052] (5) The gelled fibers were placed in 60% ethanol aqueous solution and 80% ethanol aqueous solution for 12 minutes each, and finally placed in anhydrous ethanol at room temperature for 14 hours.
[0053] (6) Then the fiber is placed in an autoclave and replaced with liquid carbon dioxide for 4 hours at a temperature of 35°C and a pressure of 8MPa. Then the temperature is raised to 45°C, the pressure is increased to 12MPa and maintained for 2 hours. Finally, the pressure is released to atmospheric pressure at a rate of 1MPa / h.
[0054] (7) Finally, the fiber is heat-treated in a hot air oven at 100°C for 1 hour to obtain composite aerogel fiber.
[0055] Comparative Example 1
[0056] The only difference between Comparative Example 1 and Example 1 is that modified nano zinc oxide is not added.
[0057] Comparative Example 2
[0058] The only difference between Comparative Example 2 and Example 1 is that atmospheric drying is used instead of supercritical drying, that is, it is placed in a 60°C forced-air oven and dried at atmospheric pressure for 12 hours. The remaining steps are the same as in Example 1.
[0059] Comparative Example 3
[0060] The only difference between Comparative Example 3 and Example 1 is that steps (5) and (6) are omitted.
[0061] Comparative Example 4
[0062] The only difference between Comparative Example 4 and Example 1 is that the nano zinc oxide is not modified.
[0063] The tensile strength and elongation at break were tested according to GB / T14344-2022. The fibers were woven in a plain weave with a fabric density of 120 warp threads / 10cm and 80 weft threads / 10cm. Antibacterial properties were then tested according to GB / T20944.3-2008. Table 1 below shows the performance analysis results of the embodiments and comparative examples of this invention.
[0064] Sample type Fracture strength (cN / dtex) Elongation at break (%) Inhibition rate against Staphylococcus aureus (%) Inhibition rate against Escherichia coli (%) Example 1 5.4 12.5 99.5 99.2 Example 2 5.6 13.8 99.8 99.5 Example 3 5.2 11.9 99.3 98.9 Comparative Example 1 4.8 14.2 No antibacterial properties No antibacterial properties Comparative Example 2 2.9 5.3 98.8 98.1 Comparative Example 3 3.5 7.1 97.5 96.8 Comparative Example 4 4.1 11.8 92.3 90.5
[0065] Experimental data from the examples and comparative examples show that the present invention uses nano-aramid fibers as the main skeleton material of the aerogel coating. Through the deprotonation and reprotonation process of amide groups, a three-dimensional porous network structure is constructed on the yarn surface. Nano-zinc oxide is used as the antibacterial functional component. After being modified by a silane coupling agent, it is uniformly dispersed in the three-dimensional porous network to achieve antibacterial properties. By utilizing the property that carbon dioxide has no surface tension in the supercritical state, the collapse of the aerogel network caused by capillary forces during the conventional drying process is avoided, thereby preserving the porous structure and forming a composite aerogel fiber encapsulated by aerogel.
[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A yarn-reinforced nano-aramid composite aerogel fiber, characterized in that, It includes aramid 1313 yarn and an outer aerogel layer thereon; the aerogel layer is prepared from aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, modified nano zinc oxide, anhydrous ethanol, deionized water and acetic acid; the modified nano zinc oxide is prepared from nano zinc oxide, aqueous ethanol solution, γ-aminopropyltriethoxysilane and acetic acid. The fineness of aramid 1313 yarn is 3.1-3.3 dtex; the particle size of nano zinc oxide is 20-40 nm; the length of aramid 1313 chopped fibers is 2-3 mm and the diameter is 12-14 μm. The preparation method of the yarn-reinforced nano-aramid composite aerogel fiber includes the following steps: (1) Immerse the aramid 1313 yarn in acetone solvent and clean it for 10-20 minutes under ultrasonic power of 300-400W and frequency of 40-45kHz, and then dry it at 60-80℃ for later use. Nano zinc oxide is added to an ethanol aqueous solution with a mass fraction of 50-70% and treated with an ultrasonic device with a power of 200-400W for 30-40 minutes. Then, γ-aminopropyltriethoxysilane is added, and the pH value is adjusted to 5.5-6.0 with acetic acid. The mixture is stirred in a closed container at 50-60℃ and 200-300rpm for 1-2 hours. After filtration, the mixture is washed 2-4 times with anhydrous ethanol and then placed in a vacuum drying oven at 70-80℃ for 4-6 hours to obtain modified nano zinc oxide. (2) Add aramid 1313 short-cut fibers to dimethyl sulfoxide solvent, add potassium hydroxide, stir at room temperature at 200-300 rpm for 5-7 days under nitrogen protection, then add modified nano zinc oxide, and disperse for 20-40 minutes under ultrasonic power of 400-600W to obtain nano aramid fiber sol. (3) Pass the aramid 1313 yarn pretreated in step (1) through an impregnation tank containing the nano aramid fiber sol obtained in step (2) at a speed of 0.5-1.5 m / min. (4) Pass the impregnated aramid 1313 yarn through a coagulation bath, which includes anhydrous ethanol, deionized water and acetic acid; (5) The gelled fibers are placed in 50-60% ethanol aqueous solution and 70-80% ethanol aqueous solution for 8-12 minutes each, and finally placed in anhydrous ethanol at room temperature for 10-14 hours. (6) Then the fiber is placed in an autoclave and solvent is replaced with liquid carbon dioxide. The replacement is carried out for 3-4 hours at a temperature of 30-35℃ and a pressure of 7-8MPa. Then the temperature is raised to 40-45℃ and the pressure is increased to 10-12MPa and maintained for 1-2 hours. Finally, the pressure is released to atmospheric pressure at a rate of 0.5-1MPa / h. (7) Finally, the fiber is heat-treated in a hot air oven at 80-100℃ for 0.5-1 hour to obtain composite aerogel fiber; In step (1), the mass ratio of nano zinc oxide, aqueous ethanol solution and γ-aminopropyltriethoxysilane is 100:(400-420):(5-8); In step (2), the mass ratio of aramid 1313 chopped fibers, dimethyl sulfoxide solvent, potassium hydroxide, and modified nano zinc oxide is 1:(500-520):(1-2):(0.05-0.15). In step (4), the mass ratio of anhydrous ethanol, deionized water and acetic acid in the coagulation bath is (45-55):(45-55):(10-20).
2. The yarn-reinforced nano-aramid composite aerogel fiber according to claim 1, characterized in that... The soaking time in step (3) is 2-3 minutes.
3. The yarn-reinforced nano-aramid composite aerogel fiber according to claim 1, characterized in that... In step (4), the coagulation bath stay time is 1-2 minutes.
Citation Information
Patent Citations
A kind of PBO aerogel fiber and preparation method thereof
CN119041047B
Preparation method of cyclophosphazene-based high-flame-resistance polyurea aerogel
CN109749118A
Moisture-absorbing and heat-dissipating knitted fabric and preparation method thereof
CN117431690A
Yarn-reinforced nano aramid composite aerogel fiber as well as preparation method and application thereof
CN120041969A